2016
DOI: 10.1097/aln.0000000000001279
|View full text |Cite
|
Sign up to set email alerts
|

Nondepolarizing Neuromuscular Blocking Agents, Reversal, and Risk of Postoperative Pneumonia

Abstract: Background Residual postoperative paralysis from nondepolarizing neuromuscular blocking agents (NMBAs) is a known problem. This paralysis has been associated with impaired respiratory function, but the clinical significance remains unclear. The aims of this analysis were two-fold: (1) to investigate if intermediate-acting NMBA use during surgery is associated with postoperative pneumonia and (2) to investigate if nonreversal of NMBAs is associated with postoperative pneumonia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(51 citation statements)
references
References 29 publications
0
46
0
5
Order By: Relevance
“…9,10 This is based on difficulty assuring adequate laryngeal and respiratory function in the presence of an apparently normal TOF response (visual evaluation is imprecise), with an associated risk of pneumonia. It was felt that 2.5 h after rocuronium administration, the likelihood of residual blockade was low.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 This is based on difficulty assuring adequate laryngeal and respiratory function in the presence of an apparently normal TOF response (visual evaluation is imprecise), with an associated risk of pneumonia. It was felt that 2.5 h after rocuronium administration, the likelihood of residual blockade was low.…”
Section: Discussionmentioning
confidence: 99%
“…La parálisis residual posoperatoria es un factor de riesgo bien establecido para el desarrollo de complicaciones pulmonares en el posoperatorio temprano [1][2][3][4] . La disfunción de la musculatura respiratoria y de la vía aérea superior predispone a obstrucción de la vía aérea, atelectasias, aspiración pulmonar y neumonía, al mismo tiempo que produce un deterioro de la respuesta ventilatoria a la hipoxia [2,3,[16][17][18] . En el paciente despierto, además, provoca síntomas desagradables de debilidad muscular (disturbios visuales, debilidad facial, dificultad para hablar y deglutir y sensación de fatiga generalizada) [19,20] .…”
Section: Introductionunclassified
“…En el paciente despierto, además, provoca síntomas desagradables de debilidad muscular (disturbios visuales, debilidad facial, dificultad para hablar y deglutir y sensación de fatiga generalizada) [19,20] . De manera consistente, numerosos estudios han establecido una relación entre la parálisis residual y un incremento en la morbimortalidad posoperatoria, eventos respiratorios críticos y un incremento de la estancia en la UCPA [1][2][3][4][16][17][18][19][20][21][22] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…However current studies identified that appropriate dosing of neostigmine for reversing of residual paralysis is able to eleminate effectively the incidence of respiratory complications and that the application of sugammadex 1.0 mg kg -1 at a TOFR ≥0.9 does not improve patient´s motor function (9,12,35,66). Murphy and colleagues revealed in a clinical setting that application of neostigmine 0.04 mg kg -1 at a TOFR of ≥0.9 did not raise the incidence of postoperative muscle weakness, hypoxemia and airway obstruction (74).…”
Section: Debatementioning
confidence: 99%